Estudo do desempenho de catalisadores tipo Ni/CexM1-xO2 (M = Zr ou Mn) na reação de oxidação parcial do metano - Silveira, Valdelice Rodrigues da (2010)
One of the main applications of methane is in the production of syngas, a mixture of hydrogen and carbon monoxide. Procedures used in this process are steam reforming, CO2 reforming, partial oxidation and autothermal reforming. The present study evaluated and compared the behavior of nickel catalysts supported on mixed oxides of cerium and manganese in the partial oxidation of methane with that of nickel catalysts supported on mixed oxides of cerium and zirconium. Mixed oxides of cerium and zirconium or cerium and manganese were synthesized using two different preparation methods, the polymeric precursor based on Pechini method and combustion reaction using a microwave. This was followed by impregnation with nickel content of 15 %. Samples were calcined at 300, 800 and 900 °C and characterized by specific surface area (SSA), X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), temperature programmed reduction (TPR) and the reaction of partial oxidation of methane. The specific areas of samples decrease with the rise in calcination temperature and after nickel impregnation. Metal-cerium solid solution was formed and the presence of other manganese species outside the solid solution structure was confirmed in the compound with the highest amounts of manganese oxides showed. With regard to scanning electron microscopy, supports based on cerium and zirconium prepared by Pechini method exhibited agglomerated particles without uniform geometry or visible pores on the surface. However, compounds containing manganese presented empty spaces in its structure. Through synthesis by combustion reaction, morphology acquired independently of the proposed composition demonstrated greater porosity in relation to Pechini synthesis. Although catalysts were prepared using different synthesis methods, the insertion of nickel showed very similar reduction profiles (TPR). In relation to nickel catalysts supported on mixed oxide of cerium and zirconium, there is an initial reduction of NiO species that present certain interaction with the support. This is followed by the reduction of Ce4+ in Ce3+ surface, with subsequent bulk reduction. For catalysts containing manganese, a reduction of nickel oxide species occurs, followed by two stages of reduction for species Mn2O3 in Mn3O4 and Mn3O4 in MnO, with subsequent reduction of bulk. With respect to partial oxidation reactions, the nickel catalyst supported on mixed oxide of cerium and zirconium, prepared using the Pechini method, exhibited CH4 conversion of approximately 80 %, with conversion of 81 % when prepared by combustion. This behavior continued for 10 hours of reaction. Manganese content was also found to directly influence catalytic activity of materials; the greater the manganese oxide content, the faster deactivation and destabilization occurred in the catalyst. In both synthesis methods, the nickel catalyst supported on mixed oxide of cerium and zirconium maintained an H2/CO ratio very close to 2 during the 10 hours of partial oxidation reaction. Samples containing manganese displayed smaller H2/CO ratios and lower performance in partial oxidation.